Hospital Pharmacist Workforce Analysis in Eleven-Year 2006-2016 at Healthcare Institutions in Saudi Arabia - Alomi, Yousef Ahmed; Alghamdi, Saeed Jamaan; Alattyh, Radi Abdullah (Journal of Pharmacy Practice and Community Medicine)
Objectives: The workforce of hospital pharmacist is one the elements of pharmacy strategic plan in Saudi Arabia. The purpose of this study is to explore hospital pharmacist’s workforce at all healthcare organization in eleven years (2006-2016) in Saudi Arabia. Methods: It is a retrospective analysis of hospital pharmacist’s workforce at all healthcare organization in the past eleven years in the period of 2006-2016 in Saudi Arabia. The analysis was carried out at nine working sectors; Ministry of Health Hospital, University Hospitals, Armed Forces Hospitals, National Gaud Hospitals, Security Forces hospitals, King Faisal Specialist hospital and research center, Royal Commission for Jubail and Yanbu Hospitals, Aramco Hospitals, and Privates hospitals. The analysis included hospital’s distribution numbers, the pharmacist distribution numbers, and gender with nationality distribution across Saudi Arabia. Result: The total numbers of hospital were 452 with governments sectors was 311 (69 %) while 141 (31%) of private Hospitals. The average numbers of hospitals were (423.45) with a range number of (384-467), and the total number was (467). The average numbers of hospital pharmacists were (4,405.27) with a range number of (3,315-6,559), and the total number was (6,559). The total gender distribution of all hospital pharmacists included male 2,630.6 (59.72%) and female 1,774.6 (40.28%). The total nationality distribution of all hospital pharmacists was Saudi 2,449 (55.59%) and non-Saudi 1,956.2 (44.41 %(. Of Saudi hospital pharmacists, 1,509.4 (61.64%) was male, and 939.5 (38.36%) was female. Conclusion: The number hospitals are tremendously increased over past years with an emphasis on MOH sector while the number of pharmacists not increased accordingly. The numbers of Saudi pharmacists at MOH hospital were more than other sectors while equal gender distributions. Targeting of Saudisitaion at all health sectors with non-MOH institutions is required.
Keywords: Hospital Pharmacist; Workforce; Manpower; Ministry of Health; Saudi Arabia